The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1039/c7cp07693b
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical behavior of Bi4B2O9towards lithium-reversible conversion reactions without nanosizing

Abstract: Conversion type materials, in particular metal fluorides, have emerged as attractive candidates for positive electrodes in next generation Li-ion batteries (LIBs). However, their practical use is being hindered by issues related to reversibility and large polarization. To minimize these issues, a few approaches enlisting the anionic network have been considered. We herein report the electrochemical properties of bismuth oxyborate BiBO and show that this compound reacts with lithium via a conversion reaction le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The voltage polarizations of 330 and 400 mV for the two reversible redox reactions in Fe 3 BO 5 oxyborate is lower compared to other Fe-based conversion materialsoxides in particularshowing voltage polarizations of more than 500 mV. ,, In analogy to kotoite-type M 3 B 2 O 6 (M = Co, Ni, and Cu), reversible cycling is expected to occur in the form of a conversion-type reaction between amorphous or nanocrystalline iron-based phases in a lithia matrix (made of Li 2 O and Li 3 BO 3 ) . The BO 3 polyanion in Fe 3 BO 5 seems to lower the voltage polarization compared to iron oxides, , as similar values were reported for other borates and oxyborates. ,, The reason for this relatively small voltage polarization is not fully understood and may, according to ref , be due to different reaction paths for lithiation and delithiation, linked to different mobilities of ionic species (here Li, O, BO 3 , and Fe).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…The voltage polarizations of 330 and 400 mV for the two reversible redox reactions in Fe 3 BO 5 oxyborate is lower compared to other Fe-based conversion materialsoxides in particularshowing voltage polarizations of more than 500 mV. ,, In analogy to kotoite-type M 3 B 2 O 6 (M = Co, Ni, and Cu), reversible cycling is expected to occur in the form of a conversion-type reaction between amorphous or nanocrystalline iron-based phases in a lithia matrix (made of Li 2 O and Li 3 BO 3 ) . The BO 3 polyanion in Fe 3 BO 5 seems to lower the voltage polarization compared to iron oxides, , as similar values were reported for other borates and oxyborates. ,, The reason for this relatively small voltage polarization is not fully understood and may, according to ref , be due to different reaction paths for lithiation and delithiation, linked to different mobilities of ionic species (here Li, O, BO 3 , and Fe).…”
Section: Resultsmentioning
confidence: 95%
“…20 The BO 3 polyanion in Fe 3 BO 5 seems to lower the voltage polarization compared to iron oxides, 13,32 as similar values were reported for other borates and oxyborates. 14,20,23 The reason for this relatively small voltage polarization is not fully understood and may, according to ref 23, be due to different reaction paths for lithiation and delithiation, linked to different mobilities of ionic species (here Li, O, BO 3 , and Fe).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is supported by the report of Bi 4 B 2 O 9 crystal, Li 3 BO 3 formation starts in 1.9 V and then Li 2 O formation progresses at a lower potential. 24) At around 1.4 V and a gently potential drop at 1.30.9 V, a reaction for reducing of Bi 2 O 3 to Bi is progressing. Li et al reported that the reaction formula (3.2, 3.3 in which the monoclinic ¡-Bi 2 O 3 or tetragonal ¢-Bi 2 O 3 is reduced to Bi proceeds 1.2 or 1.4 V. 25) However, from the crystallization behavior of this glass system, cubic Bi 2 O 3 crystal was precipitated.…”
Section: Crystallization Of Bi 2 O 3 and Bi 4 O 3 (Bo 3 )mentioning
confidence: 98%